ADDITIONAL EVIDENCE ON BOARD OWNERSHIP, FIRM PERFORMANCE AND LEVEL OF DIVERSIFICATION: THE CASE OF MALAYSIAN FIRMS - Norazlan Alias; Fauzias Mat Nor (Asian Academy of Management Journal, 2004)
This study attempts to examine the relationship between level of diversification and board ownership using bivariate correlation analysis. It further analyses using partial correlation analysis if any of the selected variables act as a common cause variable that correlates level of diversification and firm performance and develop a final estimated regression model using the selected variables extracted from 121 listed companies on the Kuala Lumpur Stock Exchanges (KLSE). Only concentration of ownership and degree of shareholders' control shows significant positive correlation. In the multiple regression analysis, dividend policy remains to be the predictor variable for Tobins' Q as a measure of firm performance but with a small R square.